Tolerance Grouping Matching Backlash Analysis of Precision Reducer based on Monte Carlo Simulation - Qiliang Wang; Xinwen Chen; Xiaofen Ye (Jixie chuandong)
Backlash is an important factor affecting the accuracy of the transmission system of the precision reducer. There are many tolerances which effect reducer backlash， if these tolerances are not differentiated and arbitrarily combined， there may be a risk of exceeding the range of the deviation. The traditional probability method used in the tolerance analysis is only based on the calculation which the tolerance meets the normal distribution， and most of these tolerance analysis are aimed at the specific type of transmission system. Based on the equal probability sampling， Monte Carlo simulation is applied to the grouping matching optimization of transmission system tolerance. The limitation of tolerance distribution type and transmission system type are overcome. Combined with an example， it shows that this method achieves the purpose of improving the precision of the precision reducer and reducing the cost.